The Contribution Of School Administrative Staff To Improving Educational Quality In The Digital - Astrella, Kahfisah; Juharyanto, Juharyanto; Burhanuddin, Burhanuddin (Universitas Negeri Malang, 2025)
The purpose of this article is to explore in greater detail how the role of school administrative staff contributes to efforts aimed at enhancing the overall quality of education, particularly in the context of the digital era. This article delves into various aspects, including the specific functions and responsibilities of administrative staff, the standards and quality of school administrative services, the ways in which administrative personnel can positively influence the improvement of school quality, and how they navigate and address the unique challenges presented by the digital age. The article is structured using a comprehensive literature review, which draws on a variety of sources such as academic books, peer-reviewed journals, past research studies, and other relevant materials that shed light on the essential functions provided by school administrative staff. After collecting the necessary references, the materials were thoroughly analyzed and synthesized to develop the discussion presented in the article. Ultimately, the article concludes that school administrative staff play a pivotal role in ensuring the efficient and effective implementation of school programs. The quality of educational administrative services is key to the smooth functioning of a school, requiring careful planning, precise execution, and thorough administration. Through their work, administrative staff contribute significantly to the improvement of educational quality, enabling a more seamless educational process and positively impacting overall school performance.